Mapping Trends and Patterns in Tuberculosis and Tobacco Use: Insights from a Bibliometric Analysis of 25 Years of Research - Meyi Yanti; Erwani Erwani; Radian Ilmaskal; Masrizal Masrizal; Sohel Rana (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Tuberculosis (TB) and tobacco use represent two of the most pervasive global health challenges, with a particularly profound impact in Low and Middle-Income Countries (LMICs). Although numerous reviews have explored the clinical and epidemiological associations between TB and smoking. A systematic analysis of publication trends is lacking. This study aims to address this gap by providing a comprehensive bibliometric analysis of the intersection between TB and tobacco use, mapping its evolution, key research themes, collaboration networks, and underexplored areas. This study utilized a bibliometric method. Data from 13,876 articles indexed in Scopus were analyzed using RStudio, VOSViewer, and OpenRefine. PLOS ONE emerged as the most prolific journal, with Wang Y being the leading author, having published 178 articles. The University of California was identified as the leading institution with 707 publications. Emerging research topics include mathematical modeling and numerical simulation, reflecting increasing attention to computational approaches in respiratory disease research. Country collaboration networks revealed the United States as the dominant contributor, with significant partnerships with African countries. These findings emphasize the importance of smoking prevention in TB control strategies, offering insights to inform public health policies and guide future research on TB and smoking’s health impacts.